Observed Emotions as Predictors of Quality of Kindergartners' Social Relationships. Issue 1 (16th February 2016) - Hernández, Maciel M.; Eisenberg, Nancy; Valiente, Carlos; Spinrad, Tracy L.; VanSchyndel, Sarah K.; Diaz, Anjolii; Silva, Kassondra M.; Berger, Rebecca H.; Southworth, Jody
Abstract: This study evaluated whether positive and anger emotional frequency (the proportion of instances an emotion was observed) and intensity (the strength of an emotion when it was observed) uniquely predicted social relationships among kindergarteners (N = 301). Emotions were observed as naturally occurring at school in the fall term and multiple reporters (peers and teachers) provided information on quality of relationships with children in the spring term. In structural equation models, positive emotion frequency, but not positive emotion intensity, was positively related to peer acceptance and negatively related to peer rejection. In contrast, the frequency of anger provided unique positive prediction of teacher–student conflict and negative prediction of peer acceptance. Furthermore, anger intensity negatively predicted teacher–student closeness and positively predicted teacher–student conflict. Implications for promoting social relationships in school are discussed.